A new pathogenic mutation of the BRCA1 gene in a patient with ovarian cancer: A case report. Issue 38 (September 2018) - Yizhen, Niu; Kemin, Li; Qingli, Li; Danqing, Wang; Rutie, Yin; Liang, Song
Abstract: Rationale: The breast cancer susceptibility gene (BRCA) is an important tumor suppressor gene and tumor susceptibility gene. Germ line BRCA1/2 mutations significantly increase the risk of breast cancer and other cancers in women. Patient concerns: A 48-year-old woman was diagnosed with breast cancer at the age of 42 and subsequently diagnosed with ovarian cancer at the age of 48. Her sister had a history of breast cancer and her mother died from ovarian cancer. Diagnoses: The patient has a family history of tumors. BRCA1/2 mutations was proved in this family members. Interventions: Sanger sequencing was used to evaluate the BRCA1/2 gene status of the patient and her sister to identify the genetic mutation sites. Outcomes: They had the same genetic mutation, namely, the c.3487_3488insA (p.Thr1163AsnfsX2) mutation in the BRCA1 gene, which is a novel mutation. Lessons: This novel mutation may be a new pathogenic mutation of the BRCA1 gene. Its relationship to breast and ovarian cancers needs to be further verified in more patient cases. Moreover, mutant protein functions in both cell and animal models are also needed.